Spinning their wheels: a reply to Jane Humphries and Benjamin Schneider - Allen, R (University of Oxford, 2018)
Jane Humphries and Benjamin Schneider have assembled several large data bases of spinners' production and wages that they believe disprove my view that high wages led to mechanization in eighteenth century England. This paper examines their data and shows that they have little value in understanding the incentives to mechanize. They collected thousands of observations of the earnings of women, but they do not know how many hours the spinners worked, so the data fail to establish whether their wage per hour (the relevant variable) was high or low. Another large sample of evidence concerned the production per day of spinners, but this information was mainly derived from schools and charity programs whose participants were selected because they were unproductive–so valid inferences about the productivity of women in general cannot be derived from these data. In addition, I present new evidence that substantiates my earlierestimates of productivity and earnings. The High Wage Hypothesis is unimpaired by the critique of Humphries and Schneider.